Serving Two Masters: The Dual Loyalties of the Nominee Director in Corporate Groups - LEE, Pey Woan (Institutional Knowledge at Singapore Management University, 2003)
A decade ago, one commentator observed that 'corporate groups have now replaced individual companies as the typical legal form for all but the smalled private enterprises". Since the phenomenon has by no means abated. On the contary, in an economic climate where the growth of enterprises at unprecedented rates is fueled by technological advances and easier access to financial markets, the corporate group form, typified by a number of companies "associated by means of holding and /or control relationships", is now unquestionalbly an important feature of the corporate landscape.